“Gentefication” in the Barrio: Examining the Relationship Between Gentrification and Homicide in East Los Angeles - Barton, Michael S. (Crime & delinquency, 2020)
Research has increasingly moved toward a consensus that violent crime declines as neighborhoods gentrify, yet some studies find the direction of this relationship varies by type of violent crime. This finding becomes even more important when connected with recent research that finds the structural influences of gang and non-gang homicide are disparate. The current study engages with research in each of these areas by examining the relationship of gentrification with levels of total, gang, and non-gang homicide in Los Angeles Police Department’s (LAPD) Hollenbeck Community Policing Area. We find gentrification was not associated with variation in total or gang homicide, but was positively associated with non-gang homicide.